Жизнь идеи в художественной форме метароманов Ф.М. Достоевского и В. Набокова - Kropaczewski, Krzysztof; Kaźmierczak, Natalia (Adam Mickiewicz University Press, Poznań, 2011)
The paper focuses on the analysis of F. Dostoyevsky's and V. Nabokov's metanovels as the phenomenon synthesizing all core values of artistic consciousness and the world of a sensitive reader. The examination of Dostoyevsky's and Nabokov's metaprose shows the coexistence of languages and cultural systems characterising both writers. The comparative method of the interpretation is utilised in order to show the unique model of intertextuality in 19th century and modern Russian literature.
LIFE OF IDEA IN POETICS OF F. DOSTOYEVSKY'S AND V. NABOKOV'S METANOVELS
Keywords: Dostoyevsky; Nabokov; Достоевский; Набоков; метароман